2015
DOI: 10.1371/journal.pone.0130716
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of an Osteoporosis Self-Assessment Tool for Taiwan (OSTAi) Postmenopausal Women-A Sub-Study of the Taiwan OsteoPorosis Survey (TOPS)

Abstract: BackgroundTo develop an OSTAi tool and compare this with the National Osteoporosis Foundation recommendations in 2013 (NOF 2013) for bone mineral density (BMD) testing among Taiwan postmenopausal women.MethodsTaiwan Osteoporosis Association (TOA) conducted a nationwide BMD survey by a bus installed with a dual energy X-ray absorptiometry (DXA) between 2008 and 2011. All of the participants completed questionnaire, which included demographics and risk factors of osteoporotic fracture in FRAX tool. We used the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 26 publications
3
20
1
Order By: Relevance
“… 9 OSTA has performed well and has been found to be cost-effective for Asians in many studies. 10 12 However, some studies reported poor results when validating OSTA’s effectiveness in identifying postmenopausal osteoporosis in a Chinese cohort. 13 , 14 Thus, we were motivated to develop a new screening tool for postmenopausal Chinese women to assess the risk of DXA-determined primary osteoporosis and chose OSTA as a comparison.…”
Section: Introductionmentioning
confidence: 99%
“… 9 OSTA has performed well and has been found to be cost-effective for Asians in many studies. 10 12 However, some studies reported poor results when validating OSTA’s effectiveness in identifying postmenopausal osteoporosis in a Chinese cohort. 13 , 14 Thus, we were motivated to develop a new screening tool for postmenopausal Chinese women to assess the risk of DXA-determined primary osteoporosis and chose OSTA as a comparison.…”
Section: Introductionmentioning
confidence: 99%
“…The current investigation was based on the Taiwan OsteoPorosis Survey (TOPS) database . In brief, a circuit program for BMD measurements was conducted by the Taiwan Osteoporosis Association (TOA) from 2008 to 2011.…”
Section: Methodsmentioning
confidence: 99%
“… 7 OSTA has been found to be cost-effective for postmenopausal OP in many studies. 8 10 However, the research about the validation of OSTA to identify primary OP in elderly male has seldom been published. Thus, we were motivated to develop a new screening tool for elderly Chinese male to assess the risk of DXA-determined primary OP and choose OSTA as a comparison.…”
Section: Introductionmentioning
confidence: 99%